Pengaruh Profitabilitas, Ukuran Perusahaan, Dan Pertumbuhan Penjualan Terhadap Struktur Modal - Arviani, Frezca Inghe; Sundari, Siti (Gorontalo Accounting Journal, 2023)
This research aims to examine the influence of profitability, company size, and sales growth on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange. Data was collected using purposive sampling. The data analysis technique in this study utilized multiple linear regression analysis with the assistance of IBM SPSS data processing. The research results indicate that, partially, profitability has an influence on the capital structure, company size influences the capital structure, and sales growth affects the capital structure. Simultaneously, profitability, company size, and sales growth also influence the capital structure of property and real estate companies.